2004
DOI: 10.1091/mbc.e04-07-0601
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Triggers an Original, Caspase-independent Pituitary Cell Death with Heterogeneous Phenotype

Abstract: Programmed cell death (PCD) is physiologically involved in the regulation of cell division and differentiation. It encompasses caspase-dependent mitochondrial and nonmitochondrial pathways. Additional caspase-independent pathways have been characterized in mitochondrial PCDs but remain hypothetical in nonmitochondrial PCDs. Epidermal growth factor (EGF) has been shown to inhibit division of pituitary somato-lactotrope cells occurring in parallel with EGF-mediated differentiation of these precursors into lactot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
28
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 48 publications
7
28
2
Order By: Relevance
“…Several studies showed that in most cells EGF is growth stimulatory and anti-apoptotic; however, a number of tumor cell lines have been shown to be killed by this peptide through unknown mechanisms [31][32][33]. Consistent with these studies, our results showed that EGF has a negative role to regulate the Mac-2BP expression, although it couldn' t detect the apoptotic process.…”
Section: G L 2 S Ir N a S T A T 3 S Ir N A H T E R T 236supporting
confidence: 88%
“…Several studies showed that in most cells EGF is growth stimulatory and anti-apoptotic; however, a number of tumor cell lines have been shown to be killed by this peptide through unknown mechanisms [31][32][33]. Consistent with these studies, our results showed that EGF has a negative role to regulate the Mac-2BP expression, although it couldn' t detect the apoptotic process.…”
Section: G L 2 S Ir N a S T A T 3 S Ir N A H T E R T 236supporting
confidence: 88%
“…Cell death induced by EGF is caspase-independent and involves a loss of MMP, but does not involve the release of cytochrome c or AIF from mitochondria. EGF-induced cell death in GH4C1 cells can be blocked by a Bcl-2 overexpression (Fombonne et al, 2004). The characterization of apoptosis in GH4C1 cells closely resembles the morphological and biochemical features of EGF-induced apoptosis in A431/ErbB-2 and SKBr3/EGFR cells.…”
Section: Discussionsupporting
confidence: 52%
“…The opening of mitochondrial pores and release of AIF and endonuclease G, which induce nuclear apoptosis, could be responsible for DNA fragmentation and chromatin condensation. However, a recent publication suggests that during EGF-induced caspase-independent apoptosis in GH4C1 cells there is no activation of AIF (Fombonne et al, 2004). Another recent publication reported that caspase inhibition prevents the mitochondrial release of AIF and endonuclease G downstream of Bax-mediated opening of pores in the mitochondrial membrane (Arnoult et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although EGFR appears to be amplified and activated in many cancers, its role in the malignant phenotype is not entirely clear (27). In most cells EGF is growth stimulatory and anti-apoptotic; however, a number of tumor cell lines have been shown to be killed by this peptide through unknown mechanisms (28,29). Interestingly, EGFR and its homologue HER2 have been reported to control various TGF-␤ responses both in vitro and in vivo (30 -34).…”
mentioning
confidence: 99%